Unpolished Thai rice prevents aberrant crypt foci formation through the invovement of β-catenin and COX-2 expression in azoxymethane-treated rats - Sareeya Reungpatthanaphong (2018)
Colorectal cancer (CRC) is a major cause of morbidity and mortality throughout the world, with chronic inflammation and diet as major causes in its development. Chemopreventive effects of natural dietary products have been the focus of studies for prevention over the past decade. This study was conducted to determine the effects of unpolished Thai rice during precancerous stage through the involvement of β-catenin, cyclooxygenase-2 (COX-2) expression and inflammatory cytokines focusing on azoxymethane (AOM)-induced aberrant crypt foci (ACF)-related to CRC. Male Sprague Dawley rats received two injections of AOM (15 mg/kg body weight) at weeks 4 and 5 while rats were treated with 20% or 70% unpolished Thai rice. The rats were sacrificed at week 38 and the colons removed for aberrant crypt foci (ACF) identification. Histopathologic changes, immunohistochemical analysis of β-catenin and COX-2 expression, and cytokine expression of proinflammatory and anti-inflammatory markers were determined. The administration of unpolished Thai rice significantly and dose dependently decreased the total number of ACF and the percentages of ACF with high-grade dysplasia. Interestingly, unpolished Thai rice suppressed the expression of β-catenin and COX-2. In addition, it also altered proinflammatory (IL-6 and IFN-γ) and anti-inflammatory (IL- 10) markers. The results suggested that unpolished Thai rice may provide a promising dietary intake for prevention during precancerous stage of CRC development, through the involvement of β-catenin and COX-2 expression, and also modulate inflammatory cytokines-related to CRC.